Solid-supported cross-metathesis and a formal alkane metathesis for the generation of biologically relevant molecules - Mendez, Luciana (2015)
Solid-phase synthetic strategies towards the generation of libraries of biologically relevant molecules were developed using olefin cross-metathesis as a key step. It is remarkably the formal alkane metathesis based on a one-pot, microwave-assisted, ruthenium catalyzed cross-metathesis and reduction to obtain Csp3-Csp3 linkages